Effect of Nigella sativa on Estradiol Levels and Menopausal Symptoms in Post-Menopausal Females - Shazo Sana; Hafiz Muhammad Umair; Muniza Saeed (Proceedings, 2021)
Introduction: Menopause is the permanent cessation of menses, typically occurs in women of 45-55 years. Menopause is associated with a number of somatic, psychological and sexual symptoms due to decline in estradiol levels resulting in poor quality of life of postmenopausal females.